Lexical studies of Filipino person descriptors: Adding personality-relevant social and physical attributes - Imperio, Shellah Myra (Animo Repository, 2008)
Lexical studies have focused on traits. In the Filipino language, we investigated whether additional dimensions can be identified when personality-relevant terms for social roles, statuses and effects, plus physical attributes, are included. Filipino students (N = 496) rated themselves on 268 such terms, plus 253 markers of trait and evaluative dimensions. We identified 10 dimensions of social and physical attributes - Prominence, Uselessness, Attractiveness, Respectability, Uniqueness, Destructiveness, Presentableness, Strength, Dangerousness and Charisma. Most of these dimensions did not correspond in a one-to-one manner to Filipino or alternative trait models (Big Five, HEXACO, ML7). However, considerable redundancy was observed between the social and physical attribute dimensions and trait and evaluative dimensions. Thus, social and physical attributes communicate information about personality traits, and vice versa. Copyright © 2008 John Wiley & Sons, Ltd.